Geologi dan Analisis Pencemaran Logam Berat Menggunakan Indeks Geoakumulasi di Daerah Tulabolo Timur, Bone Bolango - Nurmasita Dewi Sahido; Yayu Indriati Arifin; Ronal Hutagalung (Journal of Applied Geoscience and Engineering, 2025)
The purpose this study is to assess geological conditions and levels of heavy metal pollution arround the artisanal gold mining area in East Tulabolo, East Suwawa District, Bone Bolango Regency, to understand its impact on the environment. This study includes geomorphological, stratighraphic, and geological structural analyses as well as measurements of heavy metal content such as arsenic (As), mercury (Hg), and lead (Pb) in river sediments. The metods used include field surveys, sampling, and laboratory analysis with ICP-MS. While pollution levels were analyzed using the Geoaccumulation Index (Igeo). The result showed that heavy metal concentrations exceeded safe limits, with the highest accumulation found in tailling sediments.. The Igeo analysis indicated a mild level of pollution due to the high concentration levels in the control area. This study emphasizes the need for sustainable waste management and ongoing contamination monitoring, including biota and groundwater sampling, to indetify risks of bioaccumulation and movement of contaminants into the wider eccosystem.